Exact soliton solutions of conformable fractional coupled Burger's equation using hyperbolic funtion approach - Yao, Shao-Wen; Rasool, Tayyiaba; Hussain, Rashida; Rezazadeh, Hadi; İnç, Mustafa (Elsevier, 2021)
In the field of nonlinear sciences many methods have been developed to obtain new explicitly exact soliton solutions. With the use of conformable derivatives, new explicit exact and soliton solutions are derived for fractional ordered coupled Burger's equations using hyperbolic function approach. Trigonometric functions are obtained which represent the wave solutions.
Keywords: Conformable derivative; Hyperbolic function approach; Fractional order coupled Burger's equation; Explicit exact soliton solutions